Fostering Multicultural and Social Justice Competence Through Counsellor Education Pedagogy - Brown, Candace B.; Collins, Sandra; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2014)
The critical incident technique was used to investigate perceptions of graduate students in two counselling psychology programs about how well the curriculum on multicultural counselling and social justice prepared them for professional practice. A thematic analysis was employed to determine themes and subthemes, which led to two important pedagogical principles. First, students gained multicultural counselling and social justice competencies through active learning principles. Second, supportive environments facilitate student development of multicultural competence and adoption of social justice values. Additional pedagogical recommendations are provided to bridge the gap between attitudes and knowledge regarding multicultural competency and social justice skills attainment. <!–[if gte mso 9]> Normal 0 false false false EN-CA JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>